Dry mouth effects from drugs used for depression, anxiety, schizophrenia and bipolar mood disorder in adults: systematic review - Cherilyn Xue Wei Teoh; Millie Thng; Serene Lau; Meng-Wong Taing; Sarah Y. Chaw; Dan Siskind; Steve Kisely (BJPsych Open, 2023)
Background Poor oral health is increasingly recognised as an important comorbidity in people with psychiatric illness. One risk factor is psychotropic-induced dry mouth.